2019
DOI: 10.1177/1024907919870928
|View full text |Cite
|
Sign up to set email alerts
|

Good Samaritan Law and bystander cardiopulmonary resuscitation: Cross-sectional study of 1223 first-aid learners in Hong Kong

Abstract: Background: Similar to many Asian cities, there is no statutory provision for the determination of the duty borne by bystander first aiders when assisting victims in Hong Kong. Objectives: The aim of this study was to explore the views of a Good Samaritan Law by first-aid learners in Hong Kong. Methods: A cross-sectional survey was conducted among first-aid course participants from the two largest training providers in Hong Kong using a self-administered questionnaire. Results: In total, 1223 questionnaires we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(59 reference statements)
0
6
0
1
Order By: Relevance
“…A local survey showed that if the Good Samaritan Law was enacted, 57% of first aid course participants indicated they would be more willing to perform bystander CPR. 21 Enacting the Good Samaritan Law locally has the potential to improve survival rates from current low rates of bystander OHCA and use of AED. 2 The quality of chest compression is affected by physical characteristics and age of students, with lower competency associated with females and those weighing less than 50 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A local survey showed that if the Good Samaritan Law was enacted, 57% of first aid course participants indicated they would be more willing to perform bystander CPR. 21 Enacting the Good Samaritan Law locally has the potential to improve survival rates from current low rates of bystander OHCA and use of AED. 2 The quality of chest compression is affected by physical characteristics and age of students, with lower competency associated with females and those weighing less than 50 kg.…”
Section: Discussionmentioning
confidence: 99%
“…A local survey showed that if the Good Samaritan Law was enacted, 57% of first aid course participants indicated they would be more willing to perform bystander CPR. 21 Enacting the Good Samaritan Law locally has the potential to improve survival rates from current low rates of bystander OHCA and use of AED. 2 …”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a previous study in Hong Kong showed that only 12.1% of the population knew the concept of a Good Samaritan Law. [ 24 ] Thailand's Good Samaritan law has been in effect since 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In some Western countries, it is fairly well known that Good Samaritan laws protect bystanders who perform CPR, whereas a previous study in Hong Kong showed that only 12.1% of the population were aware of a Good Samaritan Law concept. 25 While Good Samaritan law is enforced in Thailand in the year 2015.…”
Section: Discussionmentioning
confidence: 99%